2009
DOI: 10.1111/j.1524-4725.2009.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Split-Skin Grafting from the Scalp

Abstract: Advantages of the scalp as a donor site include rapidity of wound healing, low risk of complications, and excellent cosmetic results. The large number of hair follicles containing the epidermal stem cell pool can explain these advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 27 publications
(76 reference statements)
2
52
0
16
Order By: Relevance
“…In our study, we were able to quantitatively confirm the lower postoperative pain levels previously observed by Weyandt et al …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, we were able to quantitatively confirm the lower postoperative pain levels previously observed by Weyandt et al …”
Section: Discussionsupporting
confidence: 89%
“…For decades, dermatosurgeons have used split‐thickness skin grafts to cover tissue defects . Particular advantages of this method include the simple and gentle surgical technique as well as the possibility of closing even large defects with a low complication rate . The ideal donor site of split‐thickness skin grafts should allow for painless harvesting, and quickly heal with cosmetically pleasing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 -20 Complications such as alopecia over the donor site have been found to be rare in large studies of scalp donor sites. 21,22 Thus, although 1 of our 10 patients had visible alopecia over their donor site, we found that the scalp was a welltolerated donor site, and we will continue to use it preferentially whenever possible. One important observation on the scalp donor site was that the perimeter of the harvest area extended just beyond the hairline in two subjects.…”
Section: Discussionmentioning
confidence: 90%
“…12 This property results from its thickness, its highly vascular nature, and the high density of hair follicle and epidermal stem cells. 13 This donor site also tends to be less painful during dressings than other donor sites for STSG, such as the buttocks and inner thighs.…”
Section: Resultsmentioning
confidence: 99%